Pengaruh Penambahan Beban Latihan Double Leg Speed Hop Terhadap Daya Ledak Otot Tungkai Pemain Bola Voli - Kesumaningtyas, Rose Yulita; , Wahyuni SST.FT, SKM, M. Kes (2016)
Background: One of the basic factors that affect the ability sutau athletes in sports that require stepping games or leg muscle explosive power is like the game of volleyball. Power leg muscles play an important role which influenced the creation of a leap to be able to perform jumping smashes and blocking was perfect at the time of a match. Double Leg Speed Hop. Given exercise program serves to foster and increase leg muscle strength. Objective: To identify the trainning load addition effect double leg speed hop on leg muscle explosive power in volleyball players. Methods: The study is quasi experiment with two group pre test and post test design, the sample group I given exercise double leg speed hop without the urden and the second group performed exercises double leg speed hop with weights for 4 weeks with a frequency of 3 times a week , Data analysis using Wilcoxon test to test the effect and influence of different test using Mann Whitney test. Results: There was an effect on group I once performed Wilcoxon test p-value of 0.07. And group II result of p-value of 0.05, and there are difference in the effect after using statistical test Mann Whitney test was obtained p-value of 0.001. Conclusion: There are differences between the effects of exercise double leg hop no-load speed and workout double leg speed hop with the addition of strain on the leg muscle explosive power volleyball player.